EFFECT OF CASH MANAGEMENT ON THE FINANCIAL PERFORMANCE OF COMMERCIAL BANKS IN MOGADISHU, SOMALIA - ALI JAJALE, AHMED; IBRAHIM ALI, PROF. ABDULLAH (IJRDO - Journal of Business Management, 2017)
The general objective of this study was to establish the effect of cash management in the performance of commercial banks in Mogadishu, Somalia. Specifically, this study investigated the effects of capital adequacy, Liquidity Management, receivables management and payables management on cash management in the performance of commercial banks in Mogadishu, Somalia. The goal of the cash management function brought out the basic responsibilities of the cash manager, which, broadly speaking, take up planning, monitoring and controlling of the cash flows and the cash position of a company, while maintaining its liquidity. This study wasconducted through a descriptive study. In addition, the study employed a survey research design in data collection. The sampling procedure of this study was used nonprobability sampling procedure particularly purposive sampling or judgmental sampling. This research employed quantitative data collection method whereby data was gathered by the use of closed ended questionnaires, which were self-administered. The data collected was analyzed using the software called Statistical Package for the Social Sciences (SPSS) version 20 and results shown in terms of frequency distribution and percentages. From the data collected, 48 questionnaires were filled, 42 were returned and 6 missed which represent 88% response rate while 12% was missing. This response rate was considered satisfactory to make conclusions for the study. Mugenda and Mugenda (2003) observed that a 50% response rate was adequate, 60% was good, while 70% rated very good. This implied that based on this assertion, the response rate in this case of 88% was therefore very good. The study results supported the view that cash management drivers had a significant effect on financial performance of commercial banks in Somalia. However, the influence of each driver varied from one bank to another. It is recommended that managers should study and select the driver that best suits their banks in order to achieve maximum performance.Multiple regression analysis was performed to evaluate the relationship between the dependent variable (financial Performance of commercial banks) and the independent variables (capital adequacy, liquidity management, receivables management and payables management) and to test the research on the factors affecting financial Performance of commercial banks in Mogadishu, Somalia. Standard multiple regression analysis was conducted for hypotheses testing (Cooper & Schindler, 2013; Sekaran, 2008), while stepwise multiple regression analysis was conducted in order to establish the best combination of independent (predictor) variables would be to predict the dependent (predicted) variable and to establish the best model of the study (Cooper & Schindler, 2013).The study recommends the adoption of the cash management and financial performance of commercial banks in Mogadishu of dilemma.The cash management models were recommended as a useful design for practicing commercial banks with respect to the implementation of best practice.The study results support the view that cash management drivers have a significant effect on financial performance of commercial banks in Somalia. However, the influence of each driver varies from one bank to another. It is recommended that managers should study and select the driver that best suits their banks in order to achieve maximum performance. It was found that management policies influenced receivables management. It is recommended to the commercial banks management to ensure that the banks have put in place policies and procedures to be adhered during trade credit.The banks management is also urged to ensure that there are standardized and written manuals with the policies regarding trade credit and its management.